Respiratory muscle fatigue alters cycling performance and locomotor muscle fatigue - Fulton, T. J.; Baranauskas, M. N.; Paris, H. L.; Koceja, D. M.; Mickleborough, T. D.; Chapman, R. F. (Medicine & Science in Sports & Exercise, 2020)
Purpose: This study aimed to determine if preexisting respiratory muscle fatigue (RMF) alters motoneuronal output, locomotor muscle fatigue, and cycling performance.